The Effects of Quercetin on Apoptosis and Antioxidant Activity in a Renal Ischemia/Reperfusion Injury Animal Model - Bagheri, Amin; Radman, Ghazal; Aria, Negar; Rezaei, Fatemeh; Khajenouri, Mohammad; Ghiabi, Shamim; Bagheri, Yasin (Drug Research, 2023)
Renal ischemia-reperfusion injury (IRI) is considered as one of the most prevalent causes of acute kidney injury (AKI), which can happen in various clinical situations including hypovolemic shock, injury, thrombo-embolism, and after a kidney transplant. This paper aims to evaluate the reno-protective effects of Quercetin in induced ischemia/reperfusion injury by regulating apoptosis-related proteins, inflammatory cytokines, MMP-2, MMP-9, and nuclear factor kappa-light-chain-enhancer inactivated B cells (NF-kB) in rats. The male Wistar rats (n=32) were randomly divided into Sham, untreated IR, and Quercetin-treated IR (gavage and intraperitoneal). Quercetin was given orally and intraperitoneally one hour before inducing ischemia-reperfusion injury . After reperfusion, blood samples and kidneys were collected to assess renal function and inflammatory cytokines, apoptotic signaling proteins, and antioxidants. Urea, creatinine, and MDA levels improved in Quercetin-treated groups with different administration methods. In addition, the activities of other antioxidant in Quercetin-treated rats were higher than those in the IR group. Further, Quercetin inhibited NF-kB signaling, apoptosis-associated factors and produced matrix metalloproteinase protein in the kidneys of rats. Based on the findings, the antioxidant, anti-inflammatory, and anti-apoptotic effects of the Quercetin diminished renal ischemia-reperfusion injury in the rats significantly. It is suggested that a single dosage of Quercetin have a reno-protective impact in the case of renal I/R injury.
Keywords: Quercetin; acute renal injury; ischemia-reperfusion; oxidative stress; apoptosis